2016
DOI: 10.1088/0957-4484/27/21/215602
|View full text |Cite
|
Sign up to set email alerts
|

Growth of 2D black phosphorus film from chemical vapor deposition

Abstract: Phosphorene, a novel 2D material isolated from bulk black phosphorus (BP), is an intrinsic p-type material with a variable bandgap for a variety of applications. However, these applications are limited by the inability to isolate large films of phosphorene. Here we present an in situ chemical vapor deposition type approach that demonstrates progress towards growth of large area 2D BP with average areas >3 μm2 and thicknesses representing samples around four layers and thicker samples with average areas >100 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
227
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(231 citation statements)
references
References 40 publications
(50 reference statements)
1
227
0
3
Order By: Relevance
“…These large‐scale BP films are as thin as 2 nm but the quality is quite compromised by the amorphous feature. Some scientists turned to the traditional high‐pressure or CVT method to produce BP thin films in large scale by controlling the reaction time . By evaporating the RP powders at 400 °C followed by the condensation to a flexible substrate, RP thin films with controllable thickness can be formed; these RP thin films can then be converted to BP thin films at high pressure (10 GPa) and room temperature.…”
Section: From Bulk To 2dmentioning
confidence: 99%
“…These large‐scale BP films are as thin as 2 nm but the quality is quite compromised by the amorphous feature. Some scientists turned to the traditional high‐pressure or CVT method to produce BP thin films in large scale by controlling the reaction time . By evaporating the RP powders at 400 °C followed by the condensation to a flexible substrate, RP thin films with controllable thickness can be formed; these RP thin films can then be converted to BP thin films at high pressure (10 GPa) and room temperature.…”
Section: From Bulk To 2dmentioning
confidence: 99%
“…Interestingly, after further passivation using Al 2 O 3 , their sample with the P x O y layer showed outstanding stability (at least 30 d) under ambient conditions (see Figure 1e). [1] Recently, Smith et al [34] reported an in situ CVD method to grow large-area 2D BP directly on a silicon substrate from red phosphorus. These van der Waals heterostructures not only show improved stability but also exhibit unique properties, including high carrier mobility and hybrid functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical vapor deposition (CVD) methods that have been very successfully employed in the production of graphene24a and other 2D materials like boron nitride77 would be highly desirable. However, a first attempt in this direction using the conversion of red phosphorus into the thermodynamically more stable BP was reported 78. Beside establishing procedures for the so far elusive CVD approach, possible concepts for large‐area production of SL‐BP could involve the oxidation of surface‐supported reduced SL‐BP n − generated from the Coulomb‐force‐driven exfoliation and deposition of AM‐BPICs (AM=alkali metal, BPIC=BP intercalation compound).…”
Section: The Advent Of the Black Phosphorus Chemistrymentioning
confidence: 99%